Corneal inlay implantation complicated by infectious keratitis. Issue 2 (29th June 2015) - Duignan, Emma S; Farrell, Stephen; Treacy, Maxwell P; Fulcher, Tim; O'Brien, Paul; Power, William; Murphy, Conor C
Abstract : Background/aims: To report five cases of infectious keratitis following corneal inlay implantation for the surgical correction of presbyopia. Methods: This was a retrospective, observational case series. Five eyes of five patients were identified consecutively in two emergency departments during a 1-year period, from November 2013 to November 2014. Patients' demographics, clinical features, treatment and outcomes are described. Results: There were four female patients and one male, aged 52–64 years. Three patients had the KAMRA inlay (AcuFocus) and two had the Flexivue Microlens inlay (Presbia Coöperatief U.A.) inserted for the treatment of presbyopia and they presented from 6 days to 4 months postoperatively. Presenting uncorrected vision ranged from 6/38 to counting fingers. One patient's corneal scrapings were positive for a putatively causative organism, Corynebacterium pseudodiphtheriticum, and all patients responded to broad-spectrum fortified topical antibiotics. All patients lost vision with final uncorrected visual acuity ranging from 6/12 to 6/60 and best-corrected vision ranging from 6/7.5 to 6/12. Two patients' corneal inlays were explanted and three remained in situ at last follow-up. Conclusions: Infectious keratitis can occur at an early or late stage following corneal inlay implantation. Final visual acuity can be limited by stromal scarring; in the cases where the infiltrate was small and off the visual axis at the time of presentation, the final visual acuity was better than those patients who presented with larger lesions affecting the visual axis. Though infection may necessitate removal of the inlay, early positive response to treatment may enable the inlay to be left in situ.